Evaluation of Some Physical and Health Parameters in a Local Physical Activity Program for Seniors - Infante, Paulo (2019)
Background: About 1/5 of the population of Évora Municipality in Portugal is aged 65 and over, and there has been a continued deterioration in the ageing index (159 in 2016). Évora City Hall offers the Active Seniors program which aims to promote physical activity and healthy lifestyles among older adults (at least 55 years). This study aims to evaluate the effect on some physical and medical parameters of the participants in this program within a period of 6–12 months, showing why it is worthwhile for the municipalities to elect this type of programs. Methods: A 1-year follow-up of three groups of seniors was conducted that covered participants enrolled for the first time in the Active Seniors program and individuals who had participated in the Active Seniors program in previous years and who would maintain or increase the number of sessions per week. Participants self-reported sociodemographic and past health information and were submitted to medical tests, and anthropometric and physical evaluations. Differences in medical and physical parameters were evaluated using analysis of covariance and mixed models. Results: In just 6 months, seniors who participated in the Active Seniors program for the first time improved several medical tests results and improved their performance in physical fitness tests (all p < 0.05). The increase in the number of sessions per week decreased the systolic blood pressure values after only 6 months (p < 0.001) and improved the physical fitness tests over 12 months (p < 0.05). Conclusions: The Active Seniors program is an effective way to improve the health and physical fitness of older adults. The continuation of the program, with or without the increase in the number of weekly sessions, allows controlling the medical parameters and increasing the functional fitness of the participants. © 2019 The Author(s). Published by S. Karger AG, Basel on behalf of NOVA National School of Public Health Avaliação de alguns parâmetros físicos e de saúde num programa autárquico de atividade física para seniores Palavras chave Aptidão física · Atividade física · Envelhecimento ativo · Exercício físico · Resumo Contexto: No concelho de Évora cerca de 1/5 da população tem 65 ou mais anos e tem-se assistido a um agravamento continuado no índice de envelhecimento (159 em 2016). A Câmara Municipal de Évora oferece o programa Seniores Ativos que visa promover a atividade física e estilos de vida saudáveis junto dos adultos com pelo menos 55 anos. Este estudo visa avaliar o efeito em alguns parâmetros físicos e médicos com a participação neste programa ao longo de 6 e 12 meses, procurando também mostrar que vale a pena que os municípios apostem nesse tipo de programas. Métodos: Durante 12 meses foram seguidos três grupos de adultos, com 55 ou mais anos, que abrangiam indivíduos que participavam pela primeira vez neste programa e indivíduos que já participavam no programa Seniores Ativos em anos anteriores e que iriam manter ou aumentar o número de sessões por semana. Os participantes forneceram informações sociodemográficas e do seu estado de saúde, e foram submetidos a exames médicos e a avaliações antropométricas e físicas. As diferenças nos parâmetros médicos e físicos foram avaliadas usando testes paramétricos e não paramétricos, análise de covariância e modelos mistos. Resultados: Em apenas 6 meses, os seniores que participaram pela primeira vez no programa Seniores Ativos melhoraram os resultados dos seus testes médicos e melhoraram o seu desempenho em todos os testes de aptidão física (todos p < 0.05). O aumento do número de sessões por semana originou uma diminuição do valor da pressão sanguínea sistólica em apenas 6 meses (p < 0.001) e uma melhoria nos resultados dos testes de aptidão física ao longo dos 12 meses (p < 0.05). Conclusões: O programa Seniores Ativos é um meio eficaz para melhorar a saúde e a aptidão física dos idosos. A permanência no programa, com ou sem aumento no número de sessões semanais, permite controlar os parâmetros médicos e melhorar a aptidão funcional dos participantes.